2015
DOI: 10.1021/ac5041988
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Redox Dynamics in Living Cells with a Redox-Sensitive Red Fluorescent Protein

Abstract: Redox signaling and homeostasis are important for all forms of life on Earth. There has been great interest in monitoring redox dynamics in living cells and organisms as a mean to better understand redox biology in physiological and pathological conditions. Herein we report our recent results on the development of a genetically encoded redox-sensitive red fluorescent protein (rxRFP). We first identified a circularly permuted RFP (cpRFP) scaffold, which maintained its autocatalytic fluorescence, from a red fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 63 publications
2
58
0
1
Order By: Relevance
“…Dluciferin itself did not cause any PercevalHR fluorescence change(Figure S6A). Also, the bioluminescence reaction of FLuc-D-luciferin did not affect intracellular pH as monitored by pHRFP, a red fluorescent pH biosensor(Figure S6B) 27. It is worthwhile to note that DTZ does not induce fluorescence in live cells.…”
mentioning
confidence: 88%
“…Dluciferin itself did not cause any PercevalHR fluorescence change(Figure S6A). Also, the bioluminescence reaction of FLuc-D-luciferin did not affect intracellular pH as monitored by pHRFP, a red fluorescent pH biosensor(Figure S6B) 27. It is worthwhile to note that DTZ does not induce fluorescence in live cells.…”
mentioning
confidence: 88%
“…针 对 第 三 类 的 巯 基 类 代 谢 物 , 研 究 者 也 发 展 了 多 种 多 样 的 荧 光 蛋 白 探 针 , 包 括 rxYFP [76] , roGFP 家族 [77~79] , rxRFP [80] 以及特异性检测GSSG/GSH氧化 还原状态的荧光蛋白探针Grx1-roGFP2 [81] , 它们可以原 位、实时地监测单细胞和亚细胞水平的巯基氧化还 原状态. [40] .…”
Section: 其他氧化还原探针unclassified
“…The expansion of the color palette available to analyze oxidant events with genetically-encoded sensors is yet another contribution to the field, as in the case of rxRFP, wherein a cpRFP scaffold was utilized to develop a red fluorescent redox sensor. rxRFP is useful for monitoring the general redox health of the cell, since it has been used to detect GSSG, O2, and ONOO− in live-cell studies [180]. Sugiura et al recently reported the development of a group of proteins similar to rxYFP, known as oxidation balance sensed quenching (Oba-Q) proteins [181].…”
Section: Genetically-encoded Sensors For Redox Toxicologymentioning
confidence: 99%